2014
DOI: 10.1016/j.crohns.2013.03.013
|View full text |Cite
|
Sign up to set email alerts
|

Altered colonic mucosal availability of n-3 and n-6 polyunsaturated fatty acids in ulcerative colitis and the relationship to disease activity

Abstract: Higher AA, AA:EPA ratio, DPA and DHA and lower LA, α-LNA and EPA are seen in inflamed mucosa in UC and correlate with severity of inflammation. This suggests an alteration in fatty acid metabolism in the inflamed gut mucosa, which may offer novel targets for intervention and should be considered if nutritional strategies are used.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(45 citation statements)
references
References 34 publications
1
41
0
3
Order By: Relevance
“…Various effects of PUFA, either n-3 or n-6 PUFA have been investigated [4, 18]. Undurti et al [10] studied the effect of fish oil with a high content of n-3 PUFA on mouse gut microbiota, and found that the fish oil treatment could change the gut microbiota.…”
Section: Discussionmentioning
confidence: 99%
“…Various effects of PUFA, either n-3 or n-6 PUFA have been investigated [4, 18]. Undurti et al [10] studied the effect of fish oil with a high content of n-3 PUFA on mouse gut microbiota, and found that the fish oil treatment could change the gut microbiota.…”
Section: Discussionmentioning
confidence: 99%
“…ALA interferes with the arachidonic acid (AA) metabolism and inhibits the prostaglandin biosynthesis pathway, thereby reducing the concentration of pro-inflammatory oxylipins [2]. In addition to its effects on the formation of anti-inflammatory mediators [3,4] and its anti-hypertensive action [5][6][7], there is increasing evidence that ALA plays a role in ameliorating intestinal inflammatory disease phenotypes [8][9][10][11]. Furthermore, ALA-rich diets were reported to protect from the development of colon carcinomas [12].…”
Section: Introductionmentioning
confidence: 99%
“…It is clear from this analysis that fatty acid intake pre-illness influences the development of IBD, however, the mechanism is not yet understood. Biopsy samples from 69 UC patients and 69 controls showed that inflamed mucosa had higher AA, DPA and DHA levels and lower EPA AA:EPA ratio [92]. There were significant correlations between severity of inflammation and contents of AA, DPA and DHA (positive correlations) and of linoleic acid (LA), α-LNA and EPA (negative correlations).…”
Section: Introductionmentioning
confidence: 99%